RANGKUMAN dan pengayaan matematika kelas 1 SD Semester 1 / Jeanne Vika Traditya [et.al]; Editor, Y. Hery Kurniyanta, F.A. Dimas Andika W., Ridwan Rahadiyanto; Ilus, Harnawan - HERY Kurniyanta; DIMAS Andika; RIDWAN Rahadiyanto; HERNAWAN (Kanisius, 2016)
118 hlm. : ilus. ; 25 cm.